Relationships Between Students’ Neuroticism and Gender on the Acquisition of Scientific Process Abilities in Chemistry Qualitative Analysis - Anselem Abonyi Ugwuanyi; Florence Obiageli Ezeudu; Uzoamaka Pet Egbukwu (Journal of Research in Education and Pedagogy, 2026)
Using qualitative analysis, the study examined the relationship between neuroticism and gender on the acquisition of chemistry process skills among Nigerian senior secondary school pupils in Enugu State. The investigation was based on two research questions and two hypotheses. A correlational survey research design was employed in the study. 292 public secondary schools with 5,754 SSIII Chemistry students made up the study’s population. 360 SSIII students were included in the sample using a multistage sampling procedure. Data were gathered using the students’ neuroticism inventory (SNI) and the chemistry qualitative analysis skills rating scale. Face validity was assessed by five experts, and factor analysis was used to determine construct validity for SNI. A reliability coefficient of 0.78 for SNI items was obtained by the Cronbach's alpha method. Kendall’s coefficient of concordance (w) was used to calculate the reliability estimate of 0.92 for CQASRS. ANOVA of linear regression, Hayes Process Analysis, and Pearson’s Correlation coefficient (r) were employed to examine the hypotheses and research questions (all tested at the 0.05 level). The growth of science process abilities and students’ neuroticism were discovered to have a moderate, positive, and significant correlation in the Chemistry qualitative analysis. In the qualitative study on chemistry, gender had a significant, positive, and strong moderating effect on the connection between students’ neuroticism and ability to acquire chemistry processes. Given the findings that there is a moderate and substantial association, students should be counseled to avoid excessive levels of neuroticism, since this could negatively impact their learning of scientific method abilities. Consequently, to reduce the gender disparity observed in this study, it was also recommended that chemistry instructors promote their students’ engagement in qualitative analytical exercises.